The Financial and Economic Crisis and Developing Countries - Bruno Gurtner (Revue Internationale de Politique de Développement)
Developing countries were hit hard by the financial and economic crisis, although the impact was somewhat delayed. Every country had different challenges to master. The closer the developing countries are interconnected with the world economy, the crasser the effects. And the incipient recovery that is becoming noticeable is, for the time being, restricted to only a few countries and regions.The crisis was transmitted primarily by trade and financial flows forcing millions back into poverty. Attainment of the Millennium Development Goals is seriously jeopardised in many countries. Many developing countries did not and do not have the resources to stimulate the economy and protect their socially disadvantaged populations to the same extent as the industrialised countries. However, many countries have made considerable efforts to mitigate the effects. Developing countries have also increased their cooperation with one another and are urgently demanding a greater voice in global economic affairs.The industrialised countries are for the most part more concerned with their own problems. Their readiness to provide more extensive aid is limited. They are under pressure from the international institutions to relax their previous dominance in favour of the increasingly strong emerging countries. A shift in power and influence that was already noticeable before the financial crisis is deepening.